Previously treated latent tuberculosis infection is associated with less severe acute COVID-19: a cohort study - Scandrett, Katie; Pallett, Scott; Takwoingi, Yemisi; Cunningham, Adam F; Dedicoat, Martin; O’Shea, Matthew K (BMJ open respiratory research, 2025)
IntroductionThere is significant potential for respiratory infections, such as tuberculosis (TB) and COVID-19, to overlap but little is known about such co-infection. We aimed to study the impact of active TB and latent TB on the incidence of severe COVID-19 in a large cohort of individuals in a setting of low TB endemicity.MethodsClinical data of patients admitted to hospital with acute SARS-CoV-2 were merged with a database of patients with a history of previous or current active TB, latent TB or healthy controls. We assessed the incidence of COVID-19 in these groups, length of hospital stay, admission to the intensive care unit (ICU) and in-hospital mortality.ResultsCOVID-19 incidence among individuals with current active TB was 6.2% (12/194) and previous active TB 0.67% (30/4496). In contrast, the incidence in previously treated latent TB was 0.09% (4/4542) and among TB contacts 0.24% (34/13 391). There were similar rates of ICU admission and mortality among individuals with COVID-19 and current active TB, TB contacts and other patients. No individuals with previously treated latent TB and COVID-19 were admitted to the ICU or died.ConclusionsIndividuals with a history of latent TB seem to be at reduced risk of severe COVID-19 and have better outcomes than those with active TB and even uninfected controls. Further studies are required to understand the mechanistic basis of this observation.